Ultrasonic evaluation of the bonding between two materials in order to predict the mechanical strength of the bond - Muhammad Haziq Azmi (2019)
Adhesives have many applications in engineering, for example, in the aerospace industry for repairs. Therefore, there is a pressing need to test whether these adhesives have adhered to the surfaces and bonded well. One adhesive that is commonly used, Araldite, needs to be mixed with an appropriate amount of hardener to obtain a strong bond. As these adhesives are used between surfaces, visual checks prove to be impossible which prompts for an alternative means of checking and testing. Non-destructive testing (NDT) fits this objective, which is to deliver the ability to determine the properties of the material without causing any adverse changes to it. In this project, the design of the test specimens follows closely with the American Society for Testing and Materials (ASTM) standards, D1002 for metal lap-joint. Ultrasonic evaluation on the lap-joint area will be conducted using A-scan machine and techniques. From the A-scan machine, the percentage screen of the first back-echo and adhesive signal will be obtained. Measurement of the distances between these two signals will be used to calculate the density and acoustic velocity of the different concentrations of adhesive used. After which the specimens will go through intron lap-joint shear test in order to quantify the property of the adhesive by its strength. Based on experimental data, the results show distinct difference in signals attained from the adhesive which is prepared according to the appropriate ratio from the one that has a disproportionate amount of resin or hardener. However, it is also shown that ultrasonic evaluation using A-scan is ineffective in quantifying the strength of the adhesive. Although ultrasonic evaluation has shown to be effective detecting if an adhesive has properly cured, further studies utilising different NDT techniques and analytical techniques may be required to effectively quantify the properties of the adhesive between two adherends.